The Association Between Long Working Hours and Infertility - Joonho Ahn; Sang Ha Lee; Min Young Park; Soo Hyun Oh; Wanhyung Lee (Elsevier, 2021)
Background: This study aimed to investigate whether working long hours was related to infertility among female Korean workers, while taking age into consideration. Methods: We used data from the 2018 National Survey on Fertility and Family Health and Welfare in Korea that is a cross-sectional, nationally representative, and population-based survey. Infertility was defined as women who were not pregnant after regular unprotected intercourse for a year. Working long hours was classified as ≥52 hours, and subgroups as per age were classified on the basis of being younger or older than 40 years of age. Differences in infertility risk between the long working hour group and none were estimated in crude and fully adjusted logistic regression models with age-group stratification. Results: Of 5,909 Korean female workers, the crude and adjusted odds ratios (95% confidence intervals) of infertility for working long hours were 1.295 (0.948-1.737) and 1.303 (0.921-1.809), respectively. In the subgroup of patients below 40 years of age, the crude and adjusted odds ratios (95% confidence interval) were 1.957 (1.216-3.039) and 1.921 (1.144-3.120), whereas those aged 40 years or older had 0.994 (0.647-1.471) and 0.939 (0.560-1.501), respectively. The weighted prevalence of infertility increased as weekly working hours increased only for the younger than 40-year subgroup. Conclusions: Infertility is associated with working long hours, especially in young-aged workers. Thus, the working schedule must be structured to better suit young female workers.